Correlation of in vitro Dissolution Profiles with in vivo Pharmacokinetic Parameters of Some Commercial Brands of Aspirin Tablets Marketed in Nigeria - Bamigbola, Emmanuel Adelaja (IntechOpen, 2012)
None